Beyond the state : The colonial medical service in British Africa - Greenwood, Anna, 1952- (Book collections on Project MUSE., 2016)
This collection of essays on the Colonial Medical Service of Africa illustrates the diversity and active collaborations to be found in the untidy reality of government medical provision. The authors present important case studies covering former British colonial dependencies in Africa, including Kenya, Malawi, Nigeria, Tanzania, Uganda and Zanzibar. They reveal many new insights into the enactments of colonial policy and the ways in which colonial doctors negotiated the day-to-day reality during the height of imperial rule in Africa. The book provides essential reading for scholars and students of colonial history, medical history and colonial administration.